Agricultural-Evidence-Synthesis-Hub: v1.0.0 - Muller, Lolita; Jones, Sarah; Estrada Carmona, Natalia; Beillouin, Damien; Rosenstock, Todd; Sanchez Bogado, Andrea Cecilia (2025)
The Agricultural Evidence Synthesis Hub provides an open, reproducible workflow for systematic reviews and meta-analyses in agriculture. It standardizes search, screening, data extraction, and analysis steps across teams, combining documented methods, harmonized schemas, and optional AI tools to make evidence syntheses more efficient, comparable, and policy-relevant.